Analisis Pengaruh Variasi Kecepatan Putar dan Waktu Pengeringan Jagung Terhadap Effisiensi Thermal Alat Rotary Dryer - Rapindo, Gepin; Izzuddin, Muhammad; Manggala, Agus; Yunanto, Isnandar; Daniar, Rima (Innovative: Journal Of Social Science Research, 2025)
Technological developments are increasingly showing very significant developments in order to simplify a process, one of which is drying using tools such as rotary dryers. The drying process is very important in reducing the moisture content in a material that functions to improve quality or extend shelf life. In this study, the effect of rotation speed and drying time on thermal efficiency will be tested. The results of the study show the influence of rotation speed and moisture content time. the lowest moisture content is at RPM 3 and the time of 120 minutes is 13.07% which has reached the SNI standard of 14%. Time also affects the drying rate, which can be seen at RPMs 1, 2 and 3 there is a decrease in drying rate of .614 kg/h m² to 0.547 kg/h m² at 120 minutes. The efficiency of the thermal rotary dryer is also affected by the rotation speed seen at RPM 3 and 20 minutes time of 69.39% while at RPM 1 and 20 minutes time of 60.92%.